On the Value of Transparency and Information Acquisition in Bargaining1. Issue 3 (August 2016) - Gehrig, Thomas; Güth, Werner; Levínský, René
Abstract: We analyze how transparency affects information acquisition in a bargaining context where proposers may choose to purchase information about the unknown outside options of their bargaining partners. Although information acquisition is excessive in all scenarios, we find that bargaining outcomes depend crucially on the transparency of the bargaining environment. In transparent games, when responders can observe whether proposers have acquired information, acceptance rates are higher. Accordingly, in transparent bargaining environments, information is more valuable, both individually and socially.